Spazio urbano e rituali di commemorazione a Hong Kong. Rappresentazioni della morte nelle Mobile Societies - Gamba, Fiorenza (Funes. Journal of narratives and social sciences, 2018)
The representations of death in contemporary society are going through very profound changes due to a very dynamic economic and technological context. Particularly in Asia, the presumed immutability of funeral rituals is giving way to a more dynamic articulation of the mental space dedicated to death. Far from urban space and physical proximity to the deads, the privacy of commemoration seems to generate a sense of belonging thanks to technologies such as mobility and virtual reality. Simulating the physical spaces of mourning has important consequences on urban space and on the narration of death. The paper aims to explore how the representation of death and the rituals of commemoration in an Asian metropolis can hold together rooted popular traditions and demands imposed by the Mobile Societies.